Pengembangan Media Pop Up Book pada Materi Sistem Tata Surya Berorientasi pada Keterampilan Ilmiah bagi Siswa Kelas VI Sekolah Dasar - Dewi Indriany; Karimatus Saidah; Muhamad Basori (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is based on the results of observations made at SDN Lirboyo 1 Kediri City, teachers in delivering material, especially the Solar System, only use the lecture method and student books. Many students have difficulty in explaining and mentioning the constituent members of the Solar System. student difficulties are seen when students are asked questions only silent, and the value at the end of learning is far from the Minimum Completeness Criteria (KKM). The formulation of the problem developed is how the process, practical validity and effectiveness of pop up book media on solar system material for grade VI elementary school students in its use as media during learning. This research uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, Develop, Implementation, and Evaluation). The subjects of this study were teachers and students of grade VI SDN Lirboyo 1 Kediri City. There are two instruments used in this study, namely using questionnaires and tests. Questionnaires are used to determine the validity and practicality of pop up book media, while tests are used to determine the effectiveness of pop up book media. The results of the pop up book media development research are as follows: (1) The results of the pop-up book media validity trial were carried out by media experts and material experts and received a percentage of 90% very valid or can be used without revision. (2) The results of the pop-up book media practicality trial in the limited trial were carried out by teachers by 92% and from students by 95%, then the results of the pop-up book media practicality in the broad trial were carried out by students by 93.5%. The percentage of scores from teachers and student responses is in the range of 81.00% - 100.00% which can be categorised as very interesting/valid. (3) The results of the effectiveness of pop-up book media obtained from the results of pretest and post test scores and getting a percentage of 81.65% are in the vulnerable range of 81.00% - 100.00% declared very effective can be used without improvement.